Las técnicas creativas para estimular la percepción sensorial en los niños de educación inicial del Centro de Educación Inicial particular Abejita Sabia del Cantón Mejía en el año lectivo 2022- 2023. - Salazar Toapanta, Rosa Edith (2023)
At the Abejita Sabía Private Initial Education Center, it was identified that after the pandemic there were problems in the sensory aspect that affected the teaching and learning process of children under five years of age. Taking into account this problem, the research carried out had the objective of designing a guide of creative techniques that are practical and fun to stimulate sensory perception in children of initial education, quantitative and qualitative methods were used that allowed to identify the shortcomings of sensory perception in the children. center children. The elaborated guide was called "Marcando Huellas" each activity of it was designed taking into account the sensory integration of Anna Jeans Ayres, where sensory systems are discussed and this was taken as the basis to unify the olfactory and gustatory systems in one.